2003
DOI: 10.1246/cl.2003.456
|View full text |Cite
|
Sign up to set email alerts
|

DNA Dissolves Single-walled Carbon Nanotubes in Water

Abstract: Transmission electron microscopy, atomic force microscopy, and UV-vis-NIR absorption spectroscopy have revealed that deoxyribonucleic acid (DNA) molecules dissolve singlewalled carbon nanotubes in an aqueous solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
179
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(184 citation statements)
references
References 18 publications
4
179
0
1
Order By: Relevance
“…In addition to surfactants, nanotubes can be stabilised in water by coating with other molecules, notably polymers [30,93] and biomolecules such as DNA [94][95][96][97][98] . SWNTs have been dispersed in water using both natural DNA [94][95][96] and short, custom-synthesised oligonucleotides [97,98] .…”
Section: Biomoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to surfactants, nanotubes can be stabilised in water by coating with other molecules, notably polymers [30,93] and biomolecules such as DNA [94][95][96][97][98] . SWNTs have been dispersed in water using both natural DNA [94][95][96] and short, custom-synthesised oligonucleotides [97,98] .…”
Section: Biomoleculesmentioning
confidence: 99%
“…SWNTs have been dispersed in water using both natural DNA [94][95][96] and short, custom-synthesised oligonucleotides [97,98] . These dispersions have the advantage of using water as the solvent, which is very safe, readily available and necessary for any potential medical or biological applications.…”
Section: Biomoleculesmentioning
confidence: 99%
“…Some types of amphiphilic polymers, such as DNA and block copolymers containing 2-methacryloyloxyethyl phosphorylcholine can efficiently disperse SWCNTs in solution media [15,16]. PVA also possesses amphiphilic properties as well as the ability to form fibers, and is one of the promising candidates for composite fibers with excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of carbon nanotubes as gene delivery vectors requires functionalization to disperse the nanotubes in aqueous media and to render them able to effectively bind to DNA. It has been reported that a variety of single-stranded DNAs, short double-stranded DNAs, and RNAs can disperse SWCNTs [14,15], and that DNA is able to insert into the opened cavity of MWCNTs in a non-specific manner [16]. However, these methodologies would require high amounts of the purified genetic material in order to functionalize and use them as gene delivery systems.…”
Section: Introductionmentioning
confidence: 99%